20% Efficient Perovskite Solar Cells with 2D Electron Transporting Layer. (6th December 2018) - Zhao, Xiaojuan; Liu, Shuangshuang; Zhang, Haitao; Chang, Sheng‐Yung; Huang, Wenchao; Zhu, Bowen; Shen, Yan; Shen, Cai; Wang, Deyu; Yang, Yang; Wang, Mingkui
Abstract: Herein, a 2D SnS2 electron transporting layer is reported via self‐assembly stacking deposition for highly efficient planar perovskite solar cells, achieving over 20% power conversion efficiency under AM 1.5 G 100 mW cm −2 light illumination. To the best of the authors' knowledge, this represents the highest efficiency that has so far been reported for perovskite solar cells using a 2D electron transporting layer. The large‐scaled 2D multilayer SnS2 sheet structure triggers a heterogeneous nucleation over the perovskite precursor film. The intermolecular Pb⋅⋅⋅S interactions between perovskite and SnS2 could passivate the interfacial trap states, which suppress charge recombination and thus facilitate electron extraction for balanced charge transport at interfaces between electron transporting layer/perovskite and hole transporting layer/perovskite. This work demonstrates that 2D materials have great potential for high‐performance perovskite solar cells. Abstract : Large‐scaled sheet structured 2D multilayer SnS2 triggers heterogeneous nucleation over the perovskite precursor film, bringing in balanced electron and hole transport at interfaces between electron transporting layers/perovskite and perovskite/hole transporting layer, and suppressing interfacial charge recombination, achieving the highest 20.12% power conversion efficiency that has so far been reported for perovskite solar cells using a 2D electron transporting layer.